2021
DOI: 10.1149/1945-7111/abf40a
|View full text |Cite
|
Sign up to set email alerts
|

An Elementary Kinetic Model for the LSCF and LSCF-CGO Electrodes of Solid Oxide Cells: Impact of Operating Conditions and Degradation on the Electrode Response

Abstract: An elementary kinetic model was developed to predict the electrochemical response of porous LSCF and LSCF-CGO electrodes. The model was validated thanks to experiments performed on symmetrical cells using a three-electrode setup. After the model calibration on polarization curves, it has been shown that the model is able to simulate accurately the experimental impedance diagram at OCP and under polarization without additional fitting.Moreover, the evolution of the electrode polarization resistance with the oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 88 publications
(316 reference statements)
2
49
0
Order By: Relevance
“…However, we have recently considered the coexistence of a second parallel pathway, called 'surface' path defined as the direct oxidation/reduction at the Triple Phase Boundaries lengths (TPBls) [21]. The predominance of one path over the other is strongly dependent on the operating conditions (polarization, temperature and oxygen partial pressure) and LSCF composition [21,22,23,24]. In this frame, it has been shown that the surface path is activated under anodic polarization (SOEC mode).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, we have recently considered the coexistence of a second parallel pathway, called 'surface' path defined as the direct oxidation/reduction at the Triple Phase Boundaries lengths (TPBls) [21]. The predominance of one path over the other is strongly dependent on the operating conditions (polarization, temperature and oxygen partial pressure) and LSCF composition [21,22,23,24]. In this frame, it has been shown that the surface path is activated under anodic polarization (SOEC mode).…”
Section: Introductionmentioning
confidence: 99%
“…In this frame, it has been shown that the surface path is activated under anodic polarization (SOEC mode). Moreover, it has been demonstrated that several steps limit simultaneously the reaction rate on the classical porous La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ electrode [24]. Therefore, a complete set of electrochemical characterizations appears to be necessary for the interpretation of the OER mechanism for LSCF.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations